R.I.P. Eliza Hart - Sheinmel, Alyssa B. (Scholastic Press, 2017)
"Ellie Sokoloff is attending Ventana Ranch School in Big Sur because she hopes that the wide-open setting will cure her claustrophobia and she was delighted to find Eliza Hart, her childhood friend, also in attendance. But Eliza has changed and for no apparent reason starts spreading rumors about Ellie, until one day she is found dead--now Ellie must find out what happened to her one-time best friend, and who killed her, not least because she herself is everybody's chief suspect"--Provided by publisher.